To see a World in a Grain of Sand. The role of the Present Moment in the study of the Educational Experience - Silvia Cescato (University of Bologna, 2015)
This article proposes a critical reflection on one of the most widely discussed topics within the theoretical debate in the humanities and social sciences over the last two centuries: the relational dimension; that is, on the one hand, the intersubjective component that encourages and accompanies the maturation of identity and awareness and, on the other, the "complex dimension" of mind/body connection that characterizes human experience moment by moment. This paper examines concepts such as "here and now", "awareness", "mind/body connection" that define our being-in-the-world as relational beings. It discusses, then, the pedagogical salience of these aspects in the fields of education and teacher training. The aim is to open a discussion - even through some examples from an empirical research in the context of early childhood services - about the hic et nuc pedagogical value in reconsidering educational actions, by promoting awareness and building intentionally relational contexts.